Long-term outcome of scleral-sutured posterior chamber intraocular lens: a case series. Issue 5 (21st August 2019) - Bausili Portabella, Maria Montserrat; Nadal, Jeroni; Alvarez de Toledo, Juan; Fideliz de la Paz, María; Barraquer, Rafael Ignacio
Abstract : Purpose: Purpose: To evaluate the long-term stability of scleral-sutured intraocular lenses (IOLs) and analyse the possible causes of suture breakage. Setting: Barraquer Institute in Barcelona, Spain. Design: Retrospective study of consecutive cases. Methods: Study of patients with scleral-sutured IOL with aphakia, subluxated or luxated IOL were included. Follow-up was longer than 6 months and patients over 18 years of age. Preoperative data (best-corrected visual acuity testing (BCVA), intraocular pressure (IOP), axial length and slit-lamp examination), intraoperative data (characteristics of the scleral flaps, suture material (Prolene or Mersilene) and scleral-sutured IOL) and postoperative data (BCVA, IOP, slit-lamp examination and complications) through 10 years were collected for analysis. Results: 345 consecutive cases of scleral-sutured IOL were included. 25 eyes underwent a second operation after a prior sutured IOL due to suture breakage (mean 40.2±39.6 months after the first surgery) and three of them needed a third surgery. Younger adults (less than 40-year old), the use of a combination of Prolene and Mersilene sutures to perform the surgery and suturing only one flap were found to have higher risk of suture breakage after a follow-up of 10 years. The probability of surviving of the scleral-sutured IOL at 10 years after surgery was 0.79. Conclusions: Scleral-sutured posterior chamber IOL in eyes with a lack of capsular support is a safe and effective procedure with a low rate of complication and stable visual acuity. Further studies with special focus on young adults or myopic eyes are required to demonstrate long-term safety in those special cases.